Starting Points? A Discussion of Contemporary Maori Society and Culture - Cleave, Peter (Te Kaharoa, 2009)
In this article, Peter Cleave explores aspects of the revitalisation of te reo Maori in a modern context, considering social, cultural, geographic and political dimensions that affect the development of te reo.